A Descriptive Study of the Eighth Grade Students' Ability in Using Connectors in Recount Text at SMP Negeri 9 Jember - Rojaningtiya, Dinik; Erlyana Fardhani, Aan; Suharjito, Bambang (Jurnal Edukasi, 2016)
This descriptive research was intended to describe the eighth grade students' ability in using connectors in a recount text at SMPN 9 Jember. The number of population was around 240 students from class VIII A up to VIII F which were chosen purposively by proportional random sampling. This research used 20% of students from each class. So, the respondents were 40 students. The data were obtained through a guided reading test, documentation, and interview. The collected data were analyzed by using a descriptive statistics. The result of the data analysis showed that the students' ability in using connectors in a recount text were categorized into fair for about 40% as many as 14 students, poor and failed that each took 30% as many as 14 and 12 students. Unfortunately, there were no students who got score between 70-79 and 80-100 under the category good and excellent. It means that the students' ability in using connectors in a recount text was not really. Keywords: Descriptive research, connectors, recount text.